2020
DOI: 10.5812/zjrms.90569
|View full text |Cite
|
Sign up to set email alerts
|

Structural Relationships Between Negative Cognitive Emotion Regulation Strategies and Symptoms of Internet Addiction: Mediating Role of Anxiety

Abstract: Background: Internet addiction is one of the most paramount problems of societies. Therefore, the knowledge of its influencing factors is of special importance. Methods: The present study was correlational in terms of goals and descriptive in terms of the data gathering procedure. The statistical population consisted of 2,000 male students and included all fourth-grade students of state high schools of Tabriz City in 2017. The sample included 246 students, selected through random cluster sampling. For the coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Specifically, in the research of Extremera et al (2019) problematic users showing significantly higher scores for maladaptive CER strategies (Rumination, Catastrophizing, Self-blame, and Other-blame). Other studies have shown that maladaptive CERS were positively associated to PIU, IA, or problematic device use (Kökönyei et al, 2019; Nosrat-Abad et al, 2020), which is consistent with the significant positive correlations we found between all maladaptive CERS and PIU. These findings suggest that problematic Internet use can be understood as a maladaptive strategy, which is used for escape from everyday problems and that partly arises because of the difficulty of using other adaptive emotional regulation strategies (e.g., Blasi et al, 2019; Brand et al, 2016; Gioia et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Specifically, in the research of Extremera et al (2019) problematic users showing significantly higher scores for maladaptive CER strategies (Rumination, Catastrophizing, Self-blame, and Other-blame). Other studies have shown that maladaptive CERS were positively associated to PIU, IA, or problematic device use (Kökönyei et al, 2019; Nosrat-Abad et al, 2020), which is consistent with the significant positive correlations we found between all maladaptive CERS and PIU. These findings suggest that problematic Internet use can be understood as a maladaptive strategy, which is used for escape from everyday problems and that partly arises because of the difficulty of using other adaptive emotional regulation strategies (e.g., Blasi et al, 2019; Brand et al, 2016; Gioia et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…According to the cognitive-behavioral model (Davis, 2001), maladaptive cognitions are a influencing factor in Internet Addiction, suggesting that high levels of Rumination might lead to more severe and durable Internet Addiction. Regarding the rest of CERS, some current results showed that all the maladaptive strategies (Self-blame, Other-blame, Catastrophizing, and Rumination) were positively related to problematic gaming on Internet (Kökönyei et al, 2019), to IA behaviors (Nosrat-Abad et al, 2020) or to Problematic Smartphone Use (Extremera et al, 2019). These findings suggest the importance of maladaptive CERS in the development and maintenance of problematic use of technology.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…As a result, those who have a lot of ruminating may have a more severe and long-lasting Internet addiction. Other recent studies have investigated both the relationship between Internet addiction and general rumination (46)(47)(48)(49)(50) as well as the specific one with so-called social media rumination, that is the propensity to continually ponder about one's social media postings, relevant situational conditions, and the ramifications of those posts, displaying a recursive cycle process with mental anguish (51)(52)(53)(54)(55).…”
Section: Introductionmentioning
confidence: 99%
“…According to Ali, argues that like drug, alcohol, and gambling addictions, certain Internet addicts' actions can have a severe impact on relationships, which can lead to difficulties finding work, unhappy marriages, and divorce [2]. Also, in adolescents, who are in a stage of physical and mental growth, their brains are developing, and external factors easily influence them.…”
Section: Manuscript Preparationmentioning
confidence: 99%